2015
DOI: 10.1016/j.molmet.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are essential for CTGF-mediated adult β-cell proliferation after injury

Abstract: ObjectivePromotion of endogenous β-cell mass expansion could facilitate regeneration in patients with diabetes. We discovered that the secreted protein CTGF (aka CCN2) promotes adult β-cell replication and mass regeneration after injury via increasing β-cell immaturity and shortening the replicative refractory period. However, the mechanism of CTGF-mediated β-cell proliferation is unknown. Here we focused on whether CTGF alters cells of the immune system to enhance β-cell replication.MethodsUsing mouse models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…Islet macrophages continuously sample antigen from beta cells [17] and, through surveying the blood vessels and islet milieu for danger signals and invading pathogens, also act as an important first line of immunological defence. Mice lacking tissue resident macrophages have reduced beta cell mass [18] and, more recently, macrophages have been found to play an important role in beta cell proliferation and regeneration in models of acute beta cell loss [19][20][21]. Many proliferative factors are released by macrophages, among them transforming growth factor β (TGFβ1) and EGF, which were reported to mediate beta cell regeneration following pancreatic duct ligation [21].…”
Section: Islet Macrophages In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Islet macrophages continuously sample antigen from beta cells [17] and, through surveying the blood vessels and islet milieu for danger signals and invading pathogens, also act as an important first line of immunological defence. Mice lacking tissue resident macrophages have reduced beta cell mass [18] and, more recently, macrophages have been found to play an important role in beta cell proliferation and regeneration in models of acute beta cell loss [19][20][21]. Many proliferative factors are released by macrophages, among them transforming growth factor β (TGFβ1) and EGF, which were reported to mediate beta cell regeneration following pancreatic duct ligation [21].…”
Section: Islet Macrophages In Health and Diseasementioning
confidence: 99%
“…Many proliferative factors are released by macrophages, among them transforming growth factor β (TGFβ1) and EGF, which were reported to mediate beta cell regeneration following pancreatic duct ligation [21]. Moreover, macrophages were shown to be crucial for beta cell proliferation following vascular endothelial growth factor-A mediated beta cell reduction [19], and for beta cell regeneration mediated by connective tissue growth factor following pancreatic ductal ligation [20].…”
Section: Islet Macrophages In Health and Diseasementioning
confidence: 99%
“…Maureen Gannon’s laboratory has reported that the secreted protein CTGF promotes adult beta cell replication and mass regeneration after injury. 12 In this session, Gannon provided new insights into beta-cell compensation mechanisms and specifically the role of CTGF together with inflammation signals in promoting expansion of functional pancreatic beta-cell mass. Tsutomu Chiba shared data on doublecortin-like kinase 1 as a marker for pancreatic intraepithelial neoplasia-initiating cells in acinar-to-ductal metaplasia.…”
Section: Session Summariesmentioning
confidence: 99%
“…In the presence of aggregates of islet amyloid polypeptide (IAPP), the pro-inflammatory state of these macrophages is enhanced, leading to IL-1 secretion that causes beta-cell dysfunction . During extreme beta-cell injury or pancreatic damage in the absence of IAPP, however, islet macrophages can produce factors that support beta-cell replication and regeneration (Criscimanna et al, 2014, Riley et al, 2015, Xiao et al, 2014, Brissova et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Various macrophage-derived growth factors are implicated in beta-cell regeneration in models of extreme beta-cell injury or during development, including TGFβ, CTGF, and IGF-2 (Riley et al, 2015, Xiao et al, 2014, Mussar et al, 2017. Here we focused on the role of macrophages in rodent models of type 2 diabetes and in response to moderate beta-cell death more representative of human disease pathology.…”
Section: Introductionmentioning
confidence: 99%